Density functional studies relevant to methanol steam reforming - Li, Xiang (2013)
In this study, methanol steam reforming (MSR) on different catalytic surfaces (Cu, PdZn, Ir, Pd and Pt) have been systematically studied by density functional methods. The adsorption studies of relevant species for MSR indicate that adsorptions on Ir (100) surface are the most stable compared to the other studied surfaces with an exception for OH. The stepped Cu(221) surface facilitates the adsorption of OH, CH2O and HCOO. And the adsorption characteristics on (100) surfaces of Ir, Pt and Pd are very similar for most species.